Education in Values: Some Ideas as an Essay - Abugattas, Gattas (2010)
This article is about the importance of the education in values in the field of law. He indicates that the values are considered as behaviors, ideas or situations positively appreciated by the human being. Having in mind that whom values is the human being the values are changing, no static. Likewise, we value the elements that are related with our living, with material or immaterial aspects related with our life. We value everything that surround us, the intersubjective relations that form the lifestyle of a human being; also, we value the same relations. These valuations are set in moral, ethical or juridical norms, which it is set as the law tridimensional origin. When we talk about the education in values, we should consider some aspects. What is it valued, which are the values that a lawyer had to had, on the latter, to handle carefully the different valuations that could have over the professional success. The main ways to teach in values is to perform a situation where do not exist values, to project injustice, lies and corruption situations (with the idea of we want what we do not have) pointing that the scenarios could change. Furthermore, to teach with the example, where the dissociation between what it is said in classes and what is done in work must not exist. The author indicates that Law is to serve people and a wrong concept of professional success could bring people to take wrong decisions. In addition, it is important to define the values that are going to be taught to the students. Finally, the virtual education could not be a useful tool for the education in values, because do not allows the human contact. It could serve for specializations courses, but not in an undergraduate level.